Hydrogel-based super-tensile flexible multifunctional input device and preparation and application thereof

Through the hydrophilic polymer-hydrophobic/electrostatic dual crosslinked hydrogel synthesis strategy, super tensile-resistant and high-sensitivity conductive hydrogels were prepared, solving the problems of insufficient tensile resistance, single functions and limited sensitivity of existing flexible touch screens and sensors, and achieving high-performance applications of flexible multifunction input devices.

CN119798515AActive Publication Date: 2025-04-11PEKING UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411879233.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-11
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing flexible touch screens and sensors have insufficient tensile resistance, single function and limited sensitivity, and the preparation method requires the addition of additional initiators, oxidants or reducing agents.

Method used

The hydrophilic polymer-hydrophobic/electrostatic dual crosslinked hydrogel synthesis strategy was adopted to prepare the precursor solution by ultrasonic dispersion method, and polymerization and crosslinking were initiated by γ ray or electron beam irradiation, and liquid metal conductive fillers were added to improve conductivity and responsiveness.

Benefits of technology

It realizes super-tension resistance, high sensitivity and multifunctional conductive hydrogel, which can continuously crack under large one-dimensional and two-dimensional stretching, and has self-healing ability, with a sensitivity of more than 10.0, and is suitable for flexible multifunctional input devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798515A_ABST
    Figure CN119798515A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogel-based super-tensile flexible multifunctional input device and preparation and application thereof. The conductive hydrogel is synthesized based on a double-crosslinking synthesis strategy of a hydrophilic polymer chain through a hydrophobic crosslinking node and a liquid metal electrostatic crosslinking node by adopting a gamma ray or electron beam radiation initiated polymerization crosslinking method, and is successfully applied to a flexible multifunctional input device. The device has ultrahigh tensile property and self-healing property, can bear large-amplitude cyclic stretching, can realize self-healing after being damaged for multiple times, and can normally work under a certain stretching amplitude and after self-healing. The device can realize two functions of a touch screen and a sensor, can realize function conversion, has the advantages of multiple functions, high sensitivity and good durability, and has a wide application prospect in stretchable flexible electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a flexible multifunctional input device, and in particular to an input device such as a flexible touch screen and a sensor assembled from a super-stretch-resistant conductive hydrogel, and a preparation method and application field thereof. Background Art

[0002] Wearable electronic devices are widely used in new fields such as human-computer interaction, smart entertainment, sports monitoring, and smart medical care. With the development of wearable electronic devices, the requirements for the sensitivity, functionality, and deformation resistance of flexible input devices are gradually increasing. How to efficiently record and translate human physical and physiological signals and generate corresponding feedback on machines and computers is a difficult point in research work. Compared with traditional human-computer interaction interfaces, hydrogel-based flexible human-computer interaction devices can better fit the skin, have strong biocompatibility, and adapt to human movement.

[0003] Flexible touch screens and flexible sensors are important human-computer interaction input devices. At present, there have been studies on the sensitivity, tensile resistance, bending resistance, compression resistance and antifreeze resistance of flexible touch screens and flexible sensors. In terms of touch screens, China's invention patent application publication CN118939142A discloses a capacitive flexible touch screen based on boron nitride, which can realize the flexible use of the touch screen. Kim et al. prepared a simple polyacrylamide / LiCl hydrogel electrolyte, which can calculate the position of human touch by applying an AC signal, realize touch control, and can be used normally under 300% one-dimensional stretching (Kim, C.-C., Lee, H.-H., Oh, KH & Sun, J.-Y. Highly Stretchable, Transparent Ionic Touch Panel. Science 353, 682-687, 2016). In terms of flexible sensors, China's invention patent application publication CN118955953A discloses a flexible cellulose hydrogel with good tensile properties and self-adhesive properties, which can be used to monitor different joint motion signals of the human body. The Chinese invention patent application publication CN118999631A discloses a silver nanowire antifreeze self-powered hydrogel flexible sensor, which can achieve self-powered sensing within 600% strain and can still monitor human movement at low temperatures. At present, the tensile strength and self-healing properties of hydrogel materials have been widely studied, but their application in flexible touch screens and flexible sensors is still lacking. In current research, the elongation at break of most hydrogel flexible touch screens and sensors does not exceed 2000%, and it is difficult to achieve self-healing. In addition, although the hydrogel flexible touch screen can achieve touch signal feedback, its functional diversity is limited and its application in flexible electronic devices is restricted. Although the flexible sensor can recognize the movement of the human body, the sensitivity is usually about 2, which is still quite different from that of traditional sensors. Moreover, the current preparation methods of hydrogel flexible touch screens and flexible sensors still have the disadvantages of requiring additional addition of initiators, oxidants or reductants. Therefore, the preparation and application of flexible touch screens and flexible sensors still have many shortcomings that deserve improvement and research. Summary of the invention

[0004] The purpose of the present invention is to design a new type of flexible multifunctional input device and prepare a hydrophilic polymer-hydrophobic crosslinker-liquid metal double cross-linked conductive hydrogel to solve the problems of insufficient tensile strength, single function and limited sensitivity of current flexible touch screens and sensors, and overcome the shortcomings of existing conductive hydrogel preparation methods that require additional addition of initiators, oxidants or reducing agents.

[0005] The present invention has developed a conductive hydrogel with super stretch resistance, high sensitivity, and both touch screen and sensor functions. First, an ultrasonic dispersion method is used to prepare a precursor solution, and then a gamma-ray or electron beam irradiation-induced polymerization and cross-linking method are used to prepare the conductive hydrogel.

[0006] Specifically, the flexible multifunctional input device proposed in the present invention is based on a conductive hydrogel mainly composed of hydrophilic polymer chains through hydrophobic cross-linking nodes and electrostatic cross-linking nodes, in which liquid metal conductive fillers are added to improve conductivity and responsiveness. On the one hand, the present invention utilizes hydrophobic cross-linking agents to polymerize to form unique hydrophobic cross-linking nodes, which can achieve elongation of hydrophilic polymer chains by depolymerization of hydrophobic cross-linking nodes under stretching. On the other hand, by introducing liquid metal for electrostatic physical cross-linking, the hydrogel has better tensile properties and self-healing ability, while improving the conductivity and responsiveness of the hydrogel. The hydrogel is connected to a specific circuit and can be assembled into a flexible input device with functions such as a flexible touch screen and a sensor.

[0007] The monomers for synthesizing the hydrophilic polymer chain need to be water-soluble and may be acrylic acid, acrylamide, methacrylamide, methacrylic acid, vinyl pyrrolidone, hydroxyethyl methacrylate, etc., preferably acrylic acid.

[0008] The hydrophobic crosslinking agent needs to have multiple crosslinking sites and be hydrophobic, and may be divinylbenzene, polyethylene glycol dimethacrylate, triallyl isocyanurate, octadiene, etc., preferably divinylbenzene.

[0009] To promote the formation of micelles by the hydrophobic crosslinking agent, a surfactant needs to be added, which may be sodium dodecyl sulfate, sodium stearate, benzalkonium chloride, trimethylbenzylammonium hydroxide, polyoxyethylene sorbitan monolaurate, etc., preferably sodium dodecyl sulfate.

[0010] Liquid metal improves the conductivity of the hydrogel and provides physical cross-linking nodes. It can be a low-melting-point alloy with a melting point of 10 to 30° C. composed of Ga and other metals in various proportions, such as GaIn alloy, GaSn alloy, GaNi alloy, GaInSn alloy, etc., preferably an alloy with a Ga:In mass ratio of 3:1.

[0011] The method for preparing the conductive hydrogel for the flexible multifunctional input device of the present invention comprises the following steps:

[0012] 1) preparing a precursor solution, wherein the precursor solution is an aqueous solution containing a water-soluble polymer monomer, a surfactant, and a hydrophobic crosslinking agent;

[0013] 2) adding liquid metal to the precursor solution prepared in step 1) and dispersing it evenly by ultrasonication;

[0014] 3) irradiating the solution prepared in step 2) with gamma rays or electron beams to prepare a conductive hydrogel.

[0015] In the precursor solution prepared in step 1) of the above method, the preferred concentration of the water-soluble polymer monomer is 30-300 g / L, the preferred concentration of the surfactant is 1-10 g / L, and the preferred concentration of the hydrophobic crosslinking agent is 0.1-10 g / L.

[0016] In step 2) of the above method, the preferred concentration of the liquid metal is 10 to 1000 mg / mL.

[0017] In step 3) of the above method, the absorbed dose rate of the gamma ray irradiation is preferably 1-100 Gy / min, and the absorbed dose is preferably 100-10000 Gy; the absorbed dose rate of the electron beam irradiation is preferably 5-20 kGy / pass, and the absorbed dose is preferably 100-10000 Gy.

[0018] The present invention tests the stretching properties and application performance of the above-mentioned flexible conductive hydrogel, which provides touch control and strain sensing applications under normal conditions and in a stretched state, and can be applied to flexible multifunctional input devices.

[0019] The flexible multifunctional input device of the present invention has the following advantages compared with the currently disclosed flexible touch screen and flexible sensor materials:

[0020] 1) The flexible multifunctional input device of the present invention has significant advantages in stretchability, self-healing, functional diversity and sensitivity;

[0021] 2) The flexible multifunctional input device of the present invention has a one-dimensional stretchability of more than 5500% and a two-dimensional stretchability of 7000%;

[0022] 3) The flexible multifunctional input device of the present invention can achieve self-healing within 30 minutes after cutting and bonding, and can recover 1600% of the tensile strainability after sufficient healing;

[0023] 4) The flexible multifunctional input device of the present invention can realize the basic functions of a touch screen, including drawing, keystroke and mouse control;

[0024] 5) The flexible multifunctional input device of the present invention can respond to strains such as stretching, compression, and bending, and the sensitivity exceeds 10.0 at a strain of 500%;

[0025] 6) The flexible multifunctional input device of the present invention can realize function switching under changing the external electrical signal input.

[0026] In summary, the present invention adopts a hydrophilic polymer-hydrophobic / electrostatic double cross-linked hydrogel synthesis strategy. The conductive hydrogel prepared by the radiation synthesis method can be applied to flexible multifunctional input devices. Breakthrough progress has been made in the stretchability of input devices. It can achieve large-scale one-dimensional and two-dimensional stretching without breaking, and can self-heal and work normally under damage. It has unique application advantages and broad application prospects in the field of flexible electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to better illustrate the technical solution of the present invention, some contents of the flexible multifunctional input device prepared by the embodiment of the present invention are illustrated with drawings, but they should not be regarded as limiting the scope of the present invention. Ordinary technicians in this field can obtain other related drawings based on these drawings without creative work.

[0028] Figure 1 , schematic diagram of the preparation method of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel in Example 1.

[0029] Figure 2 , Optical photographs of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 1, (a), (b), and (c) respectively show the flat, folded, and twisted states of the hydrogel.

[0030] Figure 3 , composition characterization of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 1, wherein (a) and (b) are X-ray photoelectron spectra of Ga and In, respectively, (c) is an X-ray diffraction pattern, and (d) is a Fourier transform infrared spectrum.

[0031] Figure 4 , the morphology and element distribution characterization of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 1, wherein (a) and (b) are scanning electron microscope images of the hydrogel, (c) is a scanning electron microscope image of the hydrogel after self-healing, and (d) is an EDS element distribution diagram in the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel.

[0032] Figure 5, the tensile properties of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different conditions in Examples 2 to 5, wherein (a) is the tensile properties of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different acrylic acid concentrations, (b) is the tensile properties of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different radiation absorbed doses, (c) is the tensile properties of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different divinylbenzene concentrations, and (d) is the tensile properties of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different GaIn alloy concentrations.

[0033] Figure 6 , the tensile curve (a) and cyclic tensile curve (b) of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 6.

[0034] Figure 7 Optical photographs of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 7 before (a) and after (b) two-dimensional stretching.

[0035] Figure 8 , compression curve of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 8.

[0036] Fig. 9 , Optical photographs of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 9 after cutting and after self-healing.

[0037] Fig.10 , circuit schematic diagram (a) and actual image (b) of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 10 assembled into a one-dimensional touch screen.

[0038] Fig.11 , touch performance of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 10 after being assembled into a one-dimensional touch screen, wherein (a) is a diagram of electrical signals at different touching positions, (b) is a diagram of signal delay after touching, (c) is a diagram of electrical signals at different touching positions under stretching, and (d) is a diagram of electrical signals at different touching positions after multiple self-healing.

[0039] Fig.12 , circuit schematic diagram (a) and actual image (b) of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 11 assembled into a two-dimensional touch screen.

[0040] Fig.13, optical photographs of the actual application of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 11 assembled into a two-dimensional touch screen, including character writing (a), key control (b) and mouse control (c).

[0041] Fig.14 , the sensing performance of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 12 assembled into a strain sensor, including resistance change graphs of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel under stretching (a), bending (b) and compression (c), and a resistance change graph after 1000 cycles of stretching (d).

[0042] Fig.15 The polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 13 was assembled into a strain sensor to record the signals of various muscle and joint movements of the human body, including swallowing (a), arm bending (b), fist clenching (c), finger bending (d), kicking (e) and stepping (f).

[0043] Fig.16 , the circuit principle diagram and function conversion schematic diagram of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared in Example 14 assembled into a flexible multifunctional input device. DETAILED DESCRIPTION

[0044] Several examples are listed below to illustrate the present invention in detail, but the present invention is not limited thereto. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified. The material testing machine used in the examples is an Instron 5969 model device from Instron Corporation of the United States, and the signal acquisition and amplification system uses a Lingzhi Electronics DAQ-122 model device.

[0045] Example 1. Preparation of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel

[0046] Preparation process Figure 1 As shown, the details are as follows:

[0047] 1) preparing a mixed aqueous solution containing 280 g / L acrylic acid, 6 g / L sodium dodecyl sulfate, and 13 g / L divinylbenzene;

[0048] 2) adding 80 g / L of GaIn alloy having a Ga:In mass ratio of 3:1 to the solution obtained in step 1), and uniformly dispersing by ultrasonication;

[0049] 3) The solution obtained in step 2) is irradiated with gamma rays at an absorbed dose rate of 16 Gy / min for 25 min to form a double cross-linked polyacrylic acid network with divinylbenzene as a chemical cross-linking node and GaIn alloy as a physical cross-linking node, thereby obtaining a polyacrylic acid-divinylbenzene-GaIn alloy hydrogel.

[0050] Figure 2 Optical photographs of the prepared polyacrylic acid-divinylbenzene-GaIn alloy hydrogel are shown, which has good flexibility and can be bent, folded and twisted freely.

[0051] Figure 3 The composition and structure of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel were demonstrated through a series of characterizations. The Ga spectrum (a) and In spectrum (b) of the X-ray photoelectron spectrum of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel showed that it had both +3 valence and 0 valence states, indicating that GaIn alloy not only maintained metal element in the hydrogel but also acted as a physical cross-linking node; (c) was the X-ray diffraction spectrum of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel, GaIn alloy, Ga metal and In metal. The crystal peak of GaIn disappeared after the alloy was formed, indicating its liquid composition; (d) was the Fourier transform infrared spectrum of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel, polyacrylic acid-divinylbenzene hydrogel, acrylic acid and divinylbenzene. The carboxyl peak of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was close to the carboxylate peak intensity, while in polyacrylic acid-divinylbenzene hydrogel and monomer acrylic acid, the carboxyl peak intensity was significantly higher than the carboxylate, confirming the physical cross-linking effect between GaIn alloy and carboxylate. The disappearance of the carbon-carbon double bond peak indicates that the polymerization and cross-linking reaction is complete and the monomer conversion is complete.

[0052] Figure 4 The morphology and composition of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel are shown. Among them, (a) shows that the hydrogel is a porous three-dimensional network structure with a pore size of about 5μm; (b) shows that the spherical GaIn alloy particles are evenly distributed on the network skeleton and in the pores, with a particle size of about 1 to 3μm; (c) shows that the hydrogel heals itself after being cut, and it can be seen that its new gel network is generated on the damaged old network, confirming its self-healing properties; (d) The element distribution on the surface of the hydrogel is analyzed by an energy spectrometer. The C element contained in the gel skeleton is evenly distributed, while Ga and In are concentrated in the spherical particles and are also evenly distributed in the hydrogel.

[0053] Example 2: Tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different acrylic acid concentrations

[0054] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthesis conditions of 140-420 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and an absorbed dose of 400 Gy. Dumbbell-shaped samples with a gauge length of 6.0 mm, a width of 2.0 mm and a thickness of 1.5 mm were cut out using a dumbbell-shaped cutter, and the tensile properties of the samples were tested using a material testing machine at a tensile rate of 50 mm / min.

[0055] Figure 5 (a) shows the tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different acrylic acid concentration conditions. When the acrylic acid concentration is 140-420 g / L, the tensile strength of the hydrogel is 20-300 kPa, and the elongation at break is 1800-5500%.

[0056] Example 3: Tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different absorption dose conditions

[0057] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthesis conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and an absorbed dose of 0 to 800 Gy. Dumbbell-shaped samples with a gauge length of 6.0 mm, a width of 2.0 mm and a thickness of 1.5 mm were cut out using a dumbbell-shaped cutter, and the tensile properties of the samples were tested using a material testing machine at a tensile rate of 50 mm / min.

[0058] Figure 5 (b) shows the tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different absorption dose conditions. When the absorption dose is ~800Gy, the tensile strength of the hydrogel is 50~300kPa and the elongation at break is 3000~5500%.

[0059] Example 4: Tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different divinylbenzene concentration conditions

[0060] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthesis conditions of 280 g / L acrylic acid, 6-26 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and an absorbed dose of 400 Gy. Dumbbell-shaped samples with a gauge length of 6.0 mm, a width of 2.0 mm and a thickness of 1.5 mm were cut out using a dumbbell-shaped cutter, and the tensile properties of the samples were tested using a material testing machine at a tensile rate of 50 mm / min.

[0061] Figure 5(c) shows the tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel prepared under different divinylbenzene concentration synthesis conditions. When the divinylbenzene concentration is 6-26 g / L, the tensile strength of the hydrogel is 70-300 kPa and the elongation at break is 3200-5500%.

[0062] Example 5: Tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different GaIn alloy concentrations

[0063] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthesis conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 0-240 g / L GaIn alloy and an absorbed dose of 400 Gy. Dumbbell-shaped samples with a gauge length of 6.0 mm, a width of 2.0 mm and a thickness of 1.5 mm were cut out using a dumbbell-shaped cutter, and the tensile properties of the samples were tested using a material testing machine at a tensile rate of 50 mm / min.

[0064] Figure 5 (d) shows the tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogels prepared under different divinylbenzene concentration conditions. When the GaIn alloy concentration is 0-240 g / L, the tensile strength of the hydrogel is 40-300 kPa, and the elongation at break is 2800-5500%.

[0065] Example 6: Tensile and cyclic tensile properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel

[0066] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. Dumbbell-shaped samples with a gauge length of 6.0 mm, a width of 2.0 mm and a thickness of 1.5 mm were cut out with a dumbbell-shaped cutter, and the tensile properties of the samples were tested at a tensile rate of 50 mm / min and the cyclic tensile properties at 4000% using a material testing machine.

[0067] Figure 6 (a) is the tensile curve of the prepared polyacrylic acid-divinylbenzene-GaIn alloy hydrogel, which can reach a tensile strength of 300 kPa and an elongation at break of 5500%. Figure 6 (b) shows the 4000% cyclic stretching curve of the prepared polyacrylic acid-divinylbenzene-GaIn alloy hydrogel for 5 times, and a hysteresis curve related to its physical cross-linking appears. The stress did not decrease during the cyclic stretching process, indicating that the large-scale stretching did not cause obvious damage to the hydrogel structure, and the stretch-recovery had good reversibility.

[0068] Example 7: Two-dimensional stretchability of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel

[0069] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. A circular sample with a diameter of 6.0 cm and a thickness of 1.5 mm was prepared using a circular mold, and the sample was multi-directionally planar stretched to a radius greater than 50 cm.

[0070] Figure 7 The two-dimensional stretching properties of the prepared polyacrylic acid-divinylbenzene-GaIn alloy hydrogel are shown. Even when the area is expanded to more than 7000% of the original area, there is still no breakage or damage, indicating that the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel has very superior two-dimensional stretchable properties.

[0071] Example 8: Compression properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel

[0072] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. A cylindrical sample with a radius of 7 mm and a height of 8 mm was cut out with a circular cutter, and the compression performance of the hydrogel was tested at a compression rate of 1.0 mm / min using a material testing machine.

[0073] Figure 8 is the compression curve of the prepared polyacrylic acid-divinylbenzene-GaIn alloy hydrogel. The hydrogel can be compressed to more than 98% and reach a compression strength of 10 MPa.

[0074] Example 9: Self-healing properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel

[0075] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. The hydrogel was cut into strips with a length of 6.0 cm, a width of 1.0 cm and a thickness of 1.5 mm, cut in the middle and then bonded. Fig. 9 It was demonstrated that the hydrogel showed obvious healing after 30 minutes of bonding.

[0076] Example 10: Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel used as a one-dimensional touch screen

[0077] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. The hydrogel was cut into strips with a length of 6.0 cm, a width of 1.0 cm and a thickness of 1.5 mm. Fig.10 The circuit connection is shown in (a), and electrodes are connected to both ends of the strip hydrogel. A current / voltage signal amplifier is connected in series and then connected to the positive electrode of a sine wave AC power supply. A signal acquisition card is used to collect and record the generated electrical signals. The negative electrode of the power supply is grounded. Fig.11 As shown in (b).

[0078] Fig.11 (a) shows the change of electrical signals when touching different positions of the hydrogel one-dimensional touch screen. V1 and V2 represent the magnitude of the electrical signals generated at both ends. When touching from left to right, the signal strength on one side increases while the signal strength on the other side decreases. Fig.11 (b) shows that the delay of signal generation does not exceed 30ms. Fig.11 (c) shows the change in the intensity of the electrical signal at different positions of the one-dimensional touch screen touching the hydrogel under 500% and 1000% stretching, indicating that the touch screen can still work normally under stretching. Fig.11 (d) shows that after self-healing 1 to 5 times, the intensity change trend of the electrical signal at the same touch position does not change significantly, indicating that it has good working stability.

[0079] Example 11: Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel used as a two-dimensional touch screen

[0080] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. The hydrogel was cut into squares with a length and width of 6.0 cm and a thickness of 1.5 mm. Fig.12 The circuit connection is shown in (a). Electrodes are connected to the four corners of the square hydrogel. A current / voltage signal amplifier is connected in series to the positive electrode of the sine wave AC power supply. A signal acquisition card is used to collect and record the generated electrical signals. The negative electrode of the power supply is grounded. Fig.12 As shown in (b).

[0081] Fig.13 (a) shows the use of the two-dimensional touch screen device to write the letters "PKU" by hand. Fig.13 (b) shows how to use the two-dimensional touch screen device to achieve a hand-touched digital key response. Fig.13(c) shows the use of the two-dimensional touch screen device to achieve hand touch mouse control and perform game operations.

[0082] Example 12: Sensing signal of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel under strain

[0083] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. The hydrogel was cut into strips with a length of 3.0 cm, a width of 1.0 cm and a thickness of 1.5 mm. The two ends of the strip hydrogel were connected to the two ends of a 0.1 V DC power supply. The generated electrical signal was collected using a data acquisition card, assembled into a strain sensor, and the current flowing through was measured and the resistance was calculated.

[0084] Fig.14 (a) shows the resistance change of the device under stretching, (b) shows the resistance change of the device under bending, (c) shows the resistance change of the device under compression, and (d) shows the resistance change of the device after 1000 stretching cycles.

[0085] Example 13: Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel used as human motion sensor

[0086] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. The hydrogel was cut into strips with a length of 3.0 cm, a width of 1.0 cm and a thickness of 1.5 mm. The two ends of the strip hydrogel were connected to the two ends of a 0.1 V DC power supply. The generated electrical signal was collected using a data acquisition card, assembled into a strain sensor, and the current flowing through was measured and the resistance was calculated.

[0087] Fig.15 The results of using the device to sense movements of multiple joints and muscles of the human body, such as (a) swallowing, (b) arm bending, (c) fist clenching, (d) finger bending, (e) kicking, and (f) stepping, are shown.

[0088] Example 14: Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel used as a flexible multifunctional input device

[0089] Polyacrylic acid-divinylbenzene-GaIn alloy hydrogel was prepared under the synthetic conditions of 280 g / L acrylic acid, 13 g / L divinylbenzene, 6 g / L sodium dodecyl sulfate, 80 g / L GaIn alloy and 400 Gy absorbed dose. The hydrogel was cut into squares with a length and width of 6.0 cm and a thickness of 1.5 mm. Fig.16 The circuit is connected as shown, the four corners of the square hydrogel are connected to the electrodes, and the current / voltage signal amplifier is connected in series and then connected to the power supply. When the touch screen function is used, the power supply inputs the same AC sinusoidal signal; when the sensing function is used, the power supply inputs a high-potential DC signal to the two electrodes on one side, and a low-potential DC signal to the two electrodes on the other side.

[0090] Fig.16 The functional switching process of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel when used as a flexible multifunctional input device is demonstrated: when an external AC signal is connected, it can be used as a touch screen to achieve operations such as music switching and volume adjustment; when an external DC signal is connected, it can be used as a motion sensor to record motion signals. By adjusting the external electrical signal, the function conversion of the same device can be achieved without changing the circuit connection.

[0091] Example 15: Tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties of polyacrylic acid-divinylbenzene-GaIn alloy hydrogel synthesized by electron beam radiation

[0092] The polyacrylic acid-divinylbenzene-GaIn alloy hydrogel synthesized under the conditions of electron beam irradiation with a dose rate of 1-10 kGy / pass and a dose of 0.1-10 kGy using an electron accelerator exhibits almost the same tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties as those synthesized by the γ-ray radiation method.

[0093] Example 16: Tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties of polyacrylamide-divinylbenzene-GaIn alloy hydrogels synthesized using gamma-ray or electron beam radiation

[0094] The polyacrylamide-divinylbenzene-GaIn alloy hydrogel synthesized by γ-ray or electron beam radiation exhibits almost the same tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties as those of the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel.

[0095] Example 17: Tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties of polyacrylic acid-polyethylene glycol dimethacrylate-GaIn alloy hydrogel synthesized by gamma ray or electron beam radiation

[0096] The polyacrylic acid-polyethylene glycol dimethacrylate-GaIn alloy hydrogel synthesized by γ-ray or electron beam irradiation exhibits almost the same tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties as the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel.

[0097] Example 18: Tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties of polyacrylic acid-divinylbenzene-GaSn alloy hydrogel synthesized by gamma ray or electron beam radiation

[0098] The polyacrylic acid-divinylbenzene-GaSn alloy hydrogel synthesized by γ-ray or electron beam irradiation exhibits almost the same tensile properties, self-healing properties, touch screen properties, strain sensing properties and functional conversion properties as the polyacrylic acid-divinylbenzene-GaIn alloy hydrogel.

Claims

1. A conductive hydrogel, mainly composed of hydrophilic polymer chains through hydrophobic cross-linking nodes and electrostatic cross-linking nodes, characterized in that: Liquid metal is added to the hydrogel as a conductive filler, wherein the hydrophobic cross-linking agent forms the hydrophobic cross-linking nodes between the hydrophilic polymer chains, and the liquid metal provides the electrostatic cross-linking nodes between the hydrophilic polymer chains.

2. The conductive hydrogel according to claim 1, characterized in that The hydrophilic polymer chain is obtained by polymerizing water-soluble polymer monomers, and the water-soluble polymer monomers are selected from one or more of the following monomers: acrylic acid, acrylamide, methacrylamide, methacrylic acid, vinyl pyrrolidone, and hydroxyethyl methacrylate.

3. The conductive hydrogel according to claim 1, characterized in that The hydrophobic crosslinking agent is selected from one or more of the following compounds: divinylbenzene, polyethylene glycol dimethacrylate, triallyl isocyanurate, octadiene.

4. The conductive hydrogel according to claim 1, characterized in that The liquid metal is a low melting point alloy composed of Ga and other metals, including but not limited to: GaIn alloy, GaSn alloy, GaNi alloy, GaInSn alloy.

5. The conductive hydrogel according to claim 4, characterized in that The liquid metal is an alloy with a Ga:In mass ratio of 3:

1.

6. The conductive hydrogel according to claim 1, characterized in that The conductive hydrogel is prepared by adding liquid metal to an aqueous solution containing a water-soluble polymer monomer, a surfactant, and a hydrophobic crosslinking agent, performing ultrasonic dispersion, and then initiating polymerization and crosslinking by irradiation with gamma rays or electron beams.

7. The method for preparing the conductive hydrogel according to any one of claims 1 to 6, comprising the following steps: 1) preparing a precursor solution, wherein the precursor solution is an aqueous solution containing a water-soluble polymer monomer, a surfactant, and a hydrophobic crosslinking agent; 2) adding liquid metal to the precursor solution prepared in step 1) and dispersing it evenly by ultrasonication; 3) irradiating the solution prepared in step 2) with gamma rays or electron beams to prepare a conductive hydrogel.

8. The preparation method according to claim 7, characterized in that: In step 1), the surfactant is selected from one or more of the following compounds: sodium dodecyl sulfate, sodium stearate, benzalkonium chloride, trimethylbenzylammonium hydroxide, polyoxyethylene sorbitan monolaurate.

9. The preparation method according to claim 7, characterized in that: In the precursor solution prepared in step 1), the concentration of the water-soluble polymer monomer is 30-300 g / L, the concentration of the surfactant is 1-10 g / L, and the concentration of the hydrophobic crosslinking agent is 0.1-10 g / L; in the solution obtained in step 2), the concentration of the liquid metal is 10-1000 mg / mL.

10. The preparation method according to claim 7, characterized in that: Step 3) gamma ray irradiation is performed with an absorbed dose rate of 1 to 100 Gy / min and an absorbed dose of 100 to 10,000 Gy; or electron beam irradiation is performed with an absorbed dose rate of 5 to 20 kGy / pass and an absorbed dose of 100 to 10,000 Gy.

11. Use of the conductive hydrogel according to any one of claims 1 to 6 in a flexible input device.

12. A flexible input device, characterized in that: The invention comprises the conductive hydrogel according to any one of claims 1 to 6 and a circuit connected thereto.

13. The flexible input device according to claim 11, characterized in that: The flexible input device is a touch screen or a sensor.

14. The flexible input device according to claim 11, characterized in that: The flexible input device is a flexible multifunctional input device, which realizes the switching of touch screen and sensor functions by changing the electrical signal input from the outside.

Citation Information

Patent Citations

  • Capacitive flexible touch screen based on boron nitride and preparation method thereof

    CN118939142A

  • Super-strain and self-adhesive flexible hydrogel as well as preparation method and application thereof

    CN118955953A

  • Silver nanowire anti-freezing self-powered hydrogel flexible sensor and preparation method and application thereof

    CN118999631A

  • Liquid metal hydrogel as well as preparation method and application thereof

    CN116462861A

  • Super-tensile integrated flexible capacitor and preparation method and application thereof

    CN117877894A